استخدام لعبة "الحية والسلم" في تعليم التصريف الاصطلاحي: حيا نلعب فنحفظ ثم نتعود - Maturedy, Faris; Abicandra, Muhammad Nidom Hamami; Baharun, Segaf; Wargadinata, Wildana (Journal of Arabic Language Teaching, 2025)
Tashrif Ishtilahi learning at Muhammadiyah Senior High School has become monotonous for students. The teacher implemented a "fun learning" strategy supported by a snakes and ladders game as instructional media to address this issue. This study aims to: describe the use of the snakes and ladders media in Tashrif Ishtilahi instruction, and examine classroom learning activities involving this media. This research adopts a qualitative approach. Data were collected through observation, interviews, and documentation. Observations and interviews were conducted to explore the classroom activities utilizing the Snakes and Ladders media, while interviews specifically captured teachers' responses to these learning activities. Documentation was used to gather visual data during the implementation process. Data were analyzed using Miles and Huberman's model, which involves three stages: data condensation, data display, and conclusion drawing. To ensure data validity, source triangulation was applied. The study yielded two main findings: the snakes and ladders media was designed using Canva, printed on A3 paper, and equipped with four tokens and one die to accommodate group play; and the gameplay resembled that of a conventional snakes and ladders game, with students required to correctly pronounce Tashrif Ishtilahi forms before moving to the next square.